Formulasi cookies bebas gluten dari tepung jagung-almond yang disuplementasi tepung kacang hijau dan variasi pemanis - Nur Aini; Budi Sustriawan; Amalia Putri Widyanti; Ervina Mela (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Cookies are a type of baked delicacy with a sweet taste and a crunchy texture. Wheat flour and white sugar are the most common ingredients in cookies. In this study, cookies' primary ingredients and sweetness were replaced with alternative ingredients to make them safer for persons who cannot consume gluten, casein, or lactose yet still want to eat cookies, such as people with gluten intolerance, celiac disease, or autism. The key ingredients in this research were corn flour, almond flour, and mung bean flour. This study also uses white sugar, palm sugar, and sorbitol as sweeteners. Block Randomized Design was the experimental design employed in this investigation. Mung bean supplementation (K) in three levels (10, 20, and 30%) and sweetener variation in three levels where the variables in this study (white sugar, palm sugar, sorbitol. Based on this factor, nine combinations of treatment were obtained. Psychochemical variables observed in this study were moisture content, ash content, fat content, reducing sugar content, dissolved protein content, and volum cookies. The result showed mung bean supplementation significantly affects fat content, and sweetener variation significantly affects moisture content, fat content, reducing sugar content, and volum of cookies. The best combination was cookies with 20% mung bean supplementation and white sugar variation. The best psychochemical characteristic had a 3.24% moisture content, 0.83% ash content, 23.04% fat content, 0.30% reducing sugar content, 3.01% dissolve protein content and 61.30% volum cookies.